2017
DOI: 10.1016/j.cor.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Routing and scheduling decisions in the hierarchical hub location problem

Abstract: a b s t r a c tHubs are facilities that consolidate and disseminate flow in many-to-many distribution systems. The hub location problem considers decisions that include the locations of hubs in a network and the allocations of demand (non-hub) nodes to these hubs. We propose a hierarchical multimodal hub network structure, and based on this network, we define a hub covering problem with a service time bound. The hierarchical network consists of three layers in which we consider a ring-star-star (RSS) network. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 32 publications
(36 reference statements)
1
34
0
Order By: Relevance
“…Random variables and fuzzy variables are the two most common ways of describing uncertainty. The objective function of this problem typically minimizes the costs of facility construction and transportation [24,[37][38][39][40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Random variables and fuzzy variables are the two most common ways of describing uncertainty. The objective function of this problem typically minimizes the costs of facility construction and transportation [24,[37][38][39][40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast to the studies reported by Kim and O'Kelly [13] and An et al [11], the present study considers multi-level and multimodal dimensions of the problem to maximize reliability. A hierarchical multimodal hub covering network with a service time bound was proposed by Dukkanci and Kara [50], wherein three di erent types of a vehicle were considered at each level: airplanes, big trucks, and pickups. They proposed a heuristic algorithm for solving the problem on a Turkish network dataset.…”
Section: Multimodal Hub Locationmentioning
confidence: 99%
“…Constraints (16)- (22) represent integrality and non-negativity of variables. Although, it should be noted that redundant constraints (19) are considered to further strengthen the LP relaxation.…”
Section: Final Decision Variablesmentioning
confidence: 99%
“…They extend their work into multi-period model and solved the model using a variation of Adaptive clonal selection algorithm [18]. Also, recently Dükkanci and Kara [19] introduced a hierarchical multimodal hub covering problem whereas the upper level is configured by ring structure instead of star structure which is used in middle and lower levels. So, the routing and scheduling constraints are added to the model.…”
Section: Introductionmentioning
confidence: 99%